2013
DOI: 10.1103/physreve.88.022129
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle fluctuations and directional correlations in driven hard-sphere glasses

Abstract: Single-particle fluctuations and directional correlations in driven hard-sphere glassesMandal, S.; Chikkadi, V.; Nienhuis, B.; Raabe, R.; Schall, P.; Varnik, F. Published in:Physical Review E DOI:10.1103/PhysRevE.88.022129 Link to publication Citation for published version (APA):Mandal, S., Chikkadi, V., Nienhuis, B., Raabe, R., Schall, P., & Varnik, F. (2013). Single-particle fluctuations and directional correlations in driven hard-sphere glasses. Physical Review E, 88, 022129. DOI: 10.1103/PhysRevE.88.022129… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
4
33
2
Order By: Relevance
“…[19], which evaluates deviations from an affine deformation on a local scale. This quantity has been used with noted success to characterize plasticity [19,20,7,21,8,9,22]; in particular, it was shown to yield results consistent with other measures of nonaffinity in Ref. [21].…”
Section: Indicator Of Plastic Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…[19], which evaluates deviations from an affine deformation on a local scale. This quantity has been used with noted success to characterize plasticity [19,20,7,21,8,9,22]; in particular, it was shown to yield results consistent with other measures of nonaffinity in Ref. [21].…”
Section: Indicator Of Plastic Activitymentioning
confidence: 91%
“…By investigating the transverse particle diffusivity, Lemaître and colleagues then showed that these correlations persist at finite shear rates [28] and at finite temperatures [29,30]. The spatial structure of these correlations was revealed by Chikkadi, Mandal, Varnik, et al [7,8]; these researchers provided convincing experimental and numerical evidence that the correlations between flow heterogeneities, quantified by D 2 min , are longranged and all the more anisotropic as shear prevails over thermal effects, i.e., at larger Peclet numbers. To do so, they monitored particle displacements in a driven "hard sphere" colloidal glass with confocal microscopy and were able to reproduce their experimental observations qualitatively with MD simulations.…”
Section: Plastic Correlatormentioning
confidence: 99%
See 1 more Smart Citation
“…Some of us recently addressed this issue for a hard-sphere glass both via computer simulations and experiments with a focus on the direction dependence of correlations and the crossover from the thermal regime of supercooled liquids to the athermal limit of strongly driven glasses [10,11]. Qualitative agreement was found between simulations and experiments regarding both the behavior of single particle fluctuations (found to be isotropic) and the anisotropy of their spatial correlations.…”
Section: Introductionmentioning
confidence: 90%
“…In athermal quasi-static simulations, Maloney and Lemaître showed that elementary events tend to organize into correlated avalanches [13]. Later, evidence for a correlation in the non-affine displacements of a colloidal glass was first reported by Chikkadi and co-workers in experiments [14] and then confirmed by Mandal and Varnik [15,16] in numerical simulations. In Ref.…”
Section: Introductionmentioning
confidence: 90%